Modelagem e controle de processos erosivos em margens de reservatórios de usinas hidrelétricas - Dewes, Junior Joel (2023)
The objectives of this research were to investigate the relationship between the soil losses observed on the banks of the Itá Hydroelectric Power Plant reservoir and the characteristics of the monitored points, and to investigate the ability of Soil Bioengineering techniques to mitigate the existing erosive processes. The object of study is the Itá HPP reservoir located on the Uruguay River between the states of Santa Catarina (SC) and Rio Grande do Sul (RS). The quantitative survey of erosions was carried out through topographic sections in 55 monitoring points distributed along the reservoir and considered two monitoring campaigns (01.2018 and 08.2021). The quantitative erosions were related to physiognomic and local variables such as fetch, slope geometry, soil properties, water oscillation, among others. The variables that were directly or indirectly related to the quantity of erosions were height and slope elevation; waves height; slope of the natural terrain; physical soil indices; fetch, shoreline perimeter and area. To control erosion processes, several Soil Bioengineering techniques with different construction designs were implemented in 4 intervention sections (ME 05, MD 01, ME 03 and ME 21) divided into a total of 15 subsections. Some techniques did not perform satisfactory in reservoir banks, especially the techniques that depend on vegetative propagation. Therefore, the use of the plant component in the interventions should be preferably through seedlings produced in a nursery. Constructive solutions for erosion control must combine inert structures with live construction materials in order to resist the stress imposed by reservoir dynamics in the long term. Works on reservoir banks must be subject to regular monitoring and maintenance campaigns, with interventions whenever is necessary to correct technical and structural failures. These measures should prioritize the control of leaf-cutting ants, the control of invasive species, seedlings replanting, cover fertilizations, the isolation of areas and executive adjustments in inert structures. It is expected that the advances obtained in relation to the understanding and control of lake erosive processes can encourage inspection agencies and entrepreneurs in the planning and implementation of mitigation measures of the environmental impacts due to the implementation and operation of large water reservoirs.